Kompetensi Pegawai dalam Meningkatkan Kualitas Pelayanan - Detson Ray Halomoan Sitorus; Dimas Agustian; Tri Anggraini (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This study aims to determine and explain the influence of employee competence on service quality. The population in this study is the community that has been served. The sample technique used in this study was non-probability sampling. The sampling technique used was purposive sampling. The respondents in this study were 96 people. The data collection used is a questionnaire. The collected data were analyzed using descriptive statistics, namely frequency analysis and simple linear regression in inferential analysis. The results showed that employee competence has a positive and significant effect on service quality, where the better the competence of employees, the higher the quality of service provided, so that the satisfaction felt by the community is determined by the extent to which the quality of service is provided. In conclusion, there is a significant influence between team member competence and service quality Keywords: Employee Competence; Public Service; Service Quality